Reallocating Agricultural Greenhouse Gas Emission in EU15 Countries - Serrão, Amilcar J (2012)
This research work uses an alternative approach for modeling agricultural greenhouse gas emissions as an undesirable output, based on the zero sum gains DEA model (ZSG-DEA BCC model). This approach reallocates agricultural greenhouse gas emissions among EU15 countries. The reallocation analysis of greenhouse gas emissions permits countries that increase their emissions negotiate the emissions reduction with the others. This negotiation process might create a quota trade system for agricultural activity.